EFL STUDENTS' EXPERIENCES AND CHALLENGES IN SPEAKING AT INTERNATIONAL CONFERENCES: A CASE STUDY AT ENGLISH LANGUAGE EDUCATION STUDY PROGRAMS STATE ISLAMIC UNIVERSITY OF MATARAMGLISH LANGUAGE EDUCATION STUDY PROGRAMS STATE ISLAMIC UNIVERSITY OF MATARAM - Dita Nabila (Journal of English Education and Literature, 2025)
Speaking at a global conference is an important event in academia, particularly for students and scholars aiming to improve their professional abilities and develop an international network. This research intends to explore the experiences and challenges that speakers face when presenting at global events, whether in-person or virtual. The study aims to examine the emotional factors, language issues, and technical challenges that come up during both the preparation and delivery of these presentations. This study explores the experiences and difficulties encountered by EFL (English as a Foreign Language) learners when presenting at global conferences, concentrating on the English Education Study Program at Universitas Islam Negeri Mataram. Utilizing a case study method, this research gathered information from interviews and questionnaires with students who attended these conferences. The results showed that students gained significant benefits from this experience, including increased confidence, communication skills, and the opportunity to build professional networks. However, they also faced various challenges, such as language barriers, anxiety, and cultural differences in presentation styles. The findings emphasize the importance of structured support and training in the development of public speaking skills.